2023
DOI: 10.1136/bmj-2023-076035
|View full text |Cite
|
Sign up to set email alerts
|

The proportions of term or late preterm births after exposure to early antenatal corticosteroids, and outcomes: systematic review and meta-analysis of 1.6 million infants

Kiran Ninan,
Anja Gojic,
Yanchen Wang
et al.

Abstract: Objective To systematically review the proportions of infants with early exposure to antenatal corticosteroids but born at term or late preterm, and short term and long term outcomes. Design Systematic review and meta-analyses. Data sources Eight databases searched from 1 January 2000 to 1 February 2023, reflecting recent perinatal care, and references of screened articles. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Notably, full-term and late preterm infants are inherently exposed to elevated levels of endogenous steroids and may additionally receive prenatal corticosteroids ( 30 ). A recent meta-analysis involving 1.6 million infants found that early prenatal exposure to corticosteroids, when compared to no direction, was associated with an increased risk of neonatal intensive care unit admissions among full-term infants (OR: 1.49, 95% CI: 1.19–1.86) ( 23 ). This highlights the pressing need for informed, evidence-based use of corticosteroids to minimize the potential for over-treatment and subsequent neonatal mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, full-term and late preterm infants are inherently exposed to elevated levels of endogenous steroids and may additionally receive prenatal corticosteroids ( 30 ). A recent meta-analysis involving 1.6 million infants found that early prenatal exposure to corticosteroids, when compared to no direction, was associated with an increased risk of neonatal intensive care unit admissions among full-term infants (OR: 1.49, 95% CI: 1.19–1.86) ( 23 ). This highlights the pressing need for informed, evidence-based use of corticosteroids to minimize the potential for over-treatment and subsequent neonatal mortality.…”
Section: Discussionmentioning
confidence: 99%
“…What is still at issue is the direct translation of randomized trial evidence into clinical practice. Can a subgroup analysis of 160 children who had been born at term in an RCT follow-up study cancel out the concerns raised by observational data on almost 700 000 infants? The dissemination of the ALPS trial results rapidly influenced practice and professional guidelines and led to a 4-fold increase in the rate of antenatal corticosteroids administration for late preterm deliveries in the US by 2018. Concomitantly, the number of term-born neonates exposed to antenatal corticosteroids more than doubled .…”
mentioning
confidence: 99%
“…The available randomized outcome data on late preterm antenatal corticosteroids cannot be further stratified by gestational age at delivery due to missing information, and the questionable stratification based on a postrandomization event (delivery date) is an additional confounding factor. Several observational studies have found an association between antenatal corticosteroids and worse neurodevelopmental and cognitive outcomes, especially in children who had been born late preterm and term, findings echoed in a recent meta-analysis . Although the level of reliability of evidence derived from observational studies is limited due to the increased potential for confounding, the number of such reports, their consistency, their different geographic provenance, and the quality of reporting make their complete dismissal impossible.…”
mentioning
confidence: 99%
“…This very high rate of preterm delivery underlines either the severity of the condition indicating inclusion in the trial or the aggressiveness of its management. In France, unlike in the United States and the ALPS trial, expectant management until 37 weeks of gestation is recommended for both prelabor rupture of membranes 5 and nonsevere preeclampsia 6 ; gestational hypertension is not even an indication for antenatal corticosteroids. Therefore, not only are further randomized trials evaluating antenatal corticosteroid efficacy for preventing respiratory morbidity associated with late preterm birth needed in lowerand middle-income countries, as suggested by the authors, but also in higher-income countries, particularly in Europe, where clinical management of the conditions indicating antenatal corticosteroids differs dramatically from that in the ALPS trial.…”
mentioning
confidence: 99%
“…The effect of antenatal steroids on twin pregnancy is complex and needs more evidence. 6 Another concern is that the study protocol published in the Clinical Trials Registry of India (CTRI/2019/09/021321) by the authors shows twin pregnancy as an exclusion. Was there a deviation from the published protocol (publication bias), and did they include twins as part of the study, which affects the external validity?…”
mentioning
confidence: 99%